Postresuscitation Changes in the Brain at the Level of Neuronal Populations: Patterns and Mechanisms - M. Sh. Avrushchenko; V. V. Moroz; I. V. Ostrova (Общая реаниматология)
The paper presents the results of a comprehensive study of postresuscitation brain changes at the level of neuronal populations. The study has revealed the general patterns and individual, typological, and sex features of changes in the neuronal populations and determined the association of neurological recovery with morphological changes of these populations. The factors influencing the resistance of neurons to ischemia/reperfusion have been found. The postresuscitation brain changes at the level of neuronal populations have been shown to be of concern in the pathogenesis of posthypoxic encephalopathies. Key words: postresuscitation period; neuronal populations; general patterns of neuronal morphological changes; individual, typological, and sex features.